Peran Pola Asuh Orangtua Terhadap Karakter Sopan Santun Siswa Kelas IV SD Inpres Beru - Yohanes Ehe Lawotan; Maria Arnoldiana Dadjan Uran (Peneliti.net, 2022)
This study aims to describe SD Inpres Beru students learning difficulties in writing skills in grade II students. This study uses qualitative research methods with data collection techniques used are interviews, observations and documentation. The respondents of this study were second grade teachers and second grade students found 7 people. The data analysis technique used in this research is research from the theory of Miles and Huberman, namely data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the role of parents and teachers in shaping the character of children's manners already knows how to respect, appreciate, help others properly and children will act or behave in accordance with what has been taught by parents and teachers at school.